2020
DOI: 10.5194/gmd-2020-59
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using SHAP to interpret XGBoost predictions of grassland degradation in Xilingol, China

Abstract: Abstract. Machine learning (ML) and data-driven approaches are increasingly used in many research areas. XGBoost is a tree boosting method that has evolved into a state-of-the-art approach for many ML challenges. However, it has rarely been used in simulations of land use change so far. Xilingol, a typical region for research on serious grassland degradation and its drivers, was selected as a case study to test whether XGBoost can provide alternative insights that conventional land-use models are unable to gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Tbb ranks second in the order of feature importance of random forests, and has a clear negative correlation with Shapley values, so the role of tbb in precipitation prediction is further explored by combining feature dependency graphs with interactions. The following analysis is carried out with Frontiers in Environmental Science frontiersin.org reference to existing studies (Wieland et al, 2020;Feng et al, 2021). In Figure 6A, tbb is the first feature and current precipitation is the second feature.…”
Section: Understanding Interactions With Tbbmentioning
confidence: 99%
“…Tbb ranks second in the order of feature importance of random forests, and has a clear negative correlation with Shapley values, so the role of tbb in precipitation prediction is further explored by combining feature dependency graphs with interactions. The following analysis is carried out with Frontiers in Environmental Science frontiersin.org reference to existing studies (Wieland et al, 2020;Feng et al, 2021). In Figure 6A, tbb is the first feature and current precipitation is the second feature.…”
Section: Understanding Interactions With Tbbmentioning
confidence: 99%
“…Beeswarm plot ( Figure 4A ) ( 54 , 55 ), indicated the range across the SHAP value and pointed out the degradation probability, expressed as the logarithm of the odds ( 56 ). We could get a general idea of the directional impact of the features in relation to the distribution of “red” and “blue” dots.…”
Section: Model Interpretationmentioning
confidence: 99%
“…Each dot on the plot represented a single observation, vertically jittered when too close to each other. Figure 4A also revealed that “mortality” included both linear-dominated relationships (in a box, Figure 4A ), such as diarrhea, sex, heart failure, etc., and non-linear-dominated relations, such as age, BMI, race, etc ( 56 ).…”
Section: Model Interpretationmentioning
confidence: 99%
“…Ding et al [28] studied the importance of the characteristics of the construction environment for driving distance using the gradient boosting model, which is one of the machine learning models. Moreover, researchers have used SHAP to validate the predictive performance of machine learning-derived land-use change predictions [29], home price prediction through a street view analysis [30], and the prediction of traffic accidents [31]. Thus, research is expanding not only by using machine learning to analyze data but also by using XAI techniques to interpret the results from machine-learning models.…”
Section: Machine-learning Model and Explainable Aimentioning
confidence: 99%